Buckle propagation of damaged SHCC sandwich pipes: Experimental tests and numerical simulation. (May 2021) - Fu, Guangming; Estefen, Segen F.; Lourenço, M.I.; Yang, Jiankun; Paz, Claudio M.; Duan, Menglan
Abstract: Sandwich pipe (SP) combining high-strength performance and thermal insulation has been considered an effective solution for oil and gas transportation in ultra-deepwater. Strain hardening cementitious composite (SHCC) is well known for its capacity to withstand both tensile load and external hydrostatic pressure. The sandwich pipe considered in the research is constituted of concentric steel pipes with SHCC annular layer. In the present research work, the SHCC was manufactured, and full scale sandwich pipes were assembled. Intact and damaged specimens were submitted to controlled external pressure in a hyperbaric chamber to obtain the collapse and propagation pressures, respectively. Modeling and simulation of the buckle propagation of the SPs were correlated with the experimental results. The results show that sandwich pipe with SHCC core has an excellent structural strength under high external pressure in both intact and damaged conditions. Moreover, the results also show that the interaction between the annular and the inner/outer pipes provides a significant contribution to the buckling resistance under propagation pressure. Highlights: The fabrication of full-scale sandwich pipes with strain hardening cementitious composite cores were proven in the laboratory. Seven full scale buckle propagation tests subjected to external pressure of sandwich pipes with SHCC have been carried out. Finite element models have been developed and validated against the experimental results. The present sandwich pipes with SHCC have excellent capacity to resist the deepwater pressure.